2021
DOI: 10.1097/ncq.0000000000000562
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Review of the Barriers and Facilitators to Nurse Engagement in Quality Improvement in the Clinical Practice Setting

Abstract: Background: Nurse engagement in quality improvement (QI) improves health care quality and outcomes but is typically low in clinical settings. Purpose: An integrative review was conducted to identify facilitators and barriers of nurse engagement in QI. Methods: This integrative review was conducted using an electronic search of databases with search terms specific to nursing engagement in QI. The Johns Hopkins Nursing Evidence-Based Practice Evidence Level and Quality Guide was used to rate quality and level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 33 publications
5
27
0
Order By: Relevance
“…Researchers concluded that leaders play a key role in fostering strong procedural justice by building a communication mechanism that gives nurses a say in decisions that affect their daily work (Djukic et al, 2021). This finding aligns with the results of our integrative review and may be a critical variable for expanding nurses' engagement (Alexander et al, 2022). Another strategy is the adoption of The American Association for Critical‐Care Nurse Standards for Establishing and Sustaining a Healthy Work Environment as a pathway for improving staff engagement, psychological safety, organisational performance and patient outcomes (American Association of Critical‐Care Nurses [AACN], 2005).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Researchers concluded that leaders play a key role in fostering strong procedural justice by building a communication mechanism that gives nurses a say in decisions that affect their daily work (Djukic et al, 2021). This finding aligns with the results of our integrative review and may be a critical variable for expanding nurses' engagement (Alexander et al, 2022). Another strategy is the adoption of The American Association for Critical‐Care Nurse Standards for Establishing and Sustaining a Healthy Work Environment as a pathway for improving staff engagement, psychological safety, organisational performance and patient outcomes (American Association of Critical‐Care Nurses [AACN], 2005).…”
Section: Discussionsupporting
confidence: 91%
“…The major themes from this study align with extensive research that has identified leadership and culture as critical drivers for QI engagement (Alexander et al, 2022;Flynn & Hatfield, 2016;Mery et al, 2017). Flynn and Hatfield (2016) are essential components of QI initiatives, it is a habitual application of QI knowledge and skills that is critical for success (Flynn & Hatfield, 2016;Lucas & Nacer, 2015;Mery et al, 2017).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The list of barriers and facilitators included on the N-QuIP tool was developed through an integrative review identifying common factors contributing to nurse engagement in QI. 6 In the event that a perceived barrier or facilitator wasn't listed, respondents could provide a free-text response, thus capturing any additional factors that may influence engagement in QI. The tool has established validity and reliability.…”
Section: Methodsmentioning
confidence: 99%